The 7th International Management Information Systems Conference 2021
DOI: 10.3390/proceedings2021074021
|View full text |Cite
|
Sign up to set email alerts
|

Optimization for Gene Selection and Cancer Classification

Abstract: Recently, gene selection has played an important role in cancer diagnosis and classification. In this study, it was studied to select high descriptive genes for use in cancer diagnosis in order to develop a classification analysis for cancer diagnosis using microarray data. For this purpose, comparative analysis and intersections of six different methods obtained by using two feature selection algorithms and three search algorithms are presented. As a result of the six different feature subset selection method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Analysis of gene expression data is a great opportunity for individuals with the disease, as treatment becomes easier once the genes most likely cause the disease are identified (Ghosh et al, 2019). It is known from the studies in the literature that the remaining genes after the selection process have higher cancer descriptors (Başeğmez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of gene expression data is a great opportunity for individuals with the disease, as treatment becomes easier once the genes most likely cause the disease are identified (Ghosh et al, 2019). It is known from the studies in the literature that the remaining genes after the selection process have higher cancer descriptors (Başeğmez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For large biological datasets, Farid et al [52] considered the K-nearest neighbours and decision trees and suggested an adaptive rule classifier. Lyu et al [65] suggested a feature selection technique that uses filters and relies on the Gram-Schmidt orthogonalization approach and the maximum information coefficient. Li et al [66] created data-driven weights for lung cancer classification according to information theory and an overlapping grouping technique.…”
Section: Introductionmentioning
confidence: 99%